Nickel-catalyzed regio- and stereoselective hydrophosphinylation of internal ynamides with H-phosphinates. Issue 49 (6th December 2018) - Kinbara, Atsushi; Kasai, Haruka; Sato, Kaede; Watanabe, Yuri; Yamagishi, Takehiro
Abstract: A method for the catalytic hydrophosphinylation of internal ynamides with H -phosphinates has been developed for the first time. The protocol employing the catalyst generated from NiBr2 and PPh3 could be applied to several types of ynamides and H -phosphinates, affording ( E )-β-aminovinylphosphinates in a highly regio- and stereoselective manner. Graphical abstract: